The diabetes community exercise programme plus usual care versus usual care in patients with type 2 diabetes: A randomised, two-arm, parallel, open-label trial. (April 2022) - Hale, L.; Higgs, C.; Gray, A.R.; Mann, J.; Mani, R.; Sullivan, T.; Terry, J.; Keen, D.; Stokes, T.
Summary: Background: Exercise is important in type 2 diabetes (T2D) management. Focussing on Māori and Pacific people and those from deprived circumstances, the Diabetes Community Exercise Programme (DCEP) was developed to engage people with T2D in exercise. We report the evaluation of whether being offered DCEP (plus usual care) was more effective than usual care in improving glycaemic control at 1-year. Methods: A randomised, two-arm, parallel, open-label trial with blinding of outcome assessor and data analyst. Adults (age ≥35 years) with T2D recruited from two New Zealand (NZ) communities were randomised, using opaque sealed envelopes and stratified by centre with random block lengths, to DCEP or usual care. DCEP comprises twice-weekly, two-hour sessions of exercise and education over 12-weeks, followed by a twice-weekly maintenance exercise class. The primary outcome was between-group differences in mean changes of glycated haemoglobin (HbA1c) from baseline to 1-year follow-up with intention-to treat analysis. This trial is registered with the Australian NZ Clinical Trials Registry (ANZCTR): ACTRN12617001624370p and is closed to new participants. Findings: From 2018 – 2019, of 294 people screened, 165 (mean age 63·8, SD16·2 years, 56% female, 78·5% European, 14% Māori, 6% Pacific, 27% most deprived) were baseline evaluated, randomised, and analysed at study end (DCEP = 83, control = 82). Multimorbidity (≥2) and polypharmacy (>5 medications) were high (82%, 69%). We found no statistically significant between-groups differences in HbA1c (mmol/mol) change at 15 months (mean 3% higher in DCEP, 95% CI 2% lower to 8% higher, p = 0·23). Twelve-week intervention adherence was good (41% attended >80% available sessions). No adverse events were reported. Interpretation: DCEP was not effective in improving glycaemic control, possibly due to insufficient exercise intensity. Our attendance demonstrated DCEP's cultural accessibility. DCEP might be good to engage in exercise marginalised people with high Hb1Ac levels, multimorbidity, and high polypharmacy. Funding: Health Research Council of New Zealand.